2014
DOI: 10.1007/s00467-014-3025-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with the use of renal replacement therapy in children receiving extracorporeal membrane oxygenation after heart surgery: a multi-institutional analysis

Abstract: We demonstrated worsening outcomes in children receiving ECMO with RRT compared to children receiving ECMO without RRT. Although the results could reflect confounding by severity of illness, they provide a rationale for prospective testing of use of RRT in critically ill children receiving ECMO with heart surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
5
14
0
Order By: Relevance
“…2,5,6,9,[11][12][13]15,16 Mortality rate in this study (49%) is similar to that reported in other studies. 4,6,7,9,12,13,15,16 An important finding of this study is that severe AKI (stages II and III) was associated with higher mortality, which is consistent with the findings reported by different authors. 2,5,6,9,[11][12][13]15,16 Our data also show that children treated with CRRT had a significantly higher mortality rate than those without CRRT, as reported in other studies.…”
Section: Evolution Of Renal Function After Ecmosupporting
confidence: 88%
See 2 more Smart Citations
“…2,5,6,9,[11][12][13]15,16 Mortality rate in this study (49%) is similar to that reported in other studies. 4,6,7,9,12,13,15,16 An important finding of this study is that severe AKI (stages II and III) was associated with higher mortality, which is consistent with the findings reported by different authors. 2,5,6,9,[11][12][13]15,16 Our data also show that children treated with CRRT had a significantly higher mortality rate than those without CRRT, as reported in other studies.…”
Section: Evolution Of Renal Function After Ecmosupporting
confidence: 88%
“…Some studies show that CRRT is associated with worsen AKI, 5,7,10,[13][14][15] whereas others show that renal function improves with CRRT. 2,3 It is difficult to argue for and against this, as urine output usually decreases after starting CRRT, and creatinine levels can be no longer considered as a marker of renal function but as a marker of proper performance of the technique.…”
Section: Renal Replacement Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal insufficiency at the time of IHCA may affect the decision to initiate or withhold mechanical support for these patients, especially in light of recent reports demonstrating worse outcomes for neonates and children with acute kidney injury requiring ECMO. 6264 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with respiratory syncytial virus infection, aspiration pneumonia, and near-fatal asthma [47] has better chances to survive while those with ARDS related to sepsis, pertussis, fungal pneumonia, disseminated herpes simplex virus infection, immunodeficiency, multiorgan failure, and longer duration of mechanical ventilation (>14 days) before ECLS deployment have higher odds of mortality [12,23,43,44,[47][48][49][50][51][52][53]. Pre-ECLS severe acidosis in addition to renal failure and need for continuous renal replacement therapy (CRRT) have been related to lower survival, longer ECLS duration, and higher complication rate [54,55].…”
Section: Pediatric Ecls (>30 Days To <18 Years)mentioning
confidence: 99%